The Effect of Sand Blasting on Shear Stress of Fiberglass - Shorea spp. Composite - Widodo, Teguh Dwi; Raharjo, Rudianto; Risonarta, Victor Yuardi; Bintarto, Redi; Kusumaningsih, Haslinda; Saputra, Muhamad Hendra (International Journal of Mechanical Engineering Technologies and Applications, 2020)
A coating is widely applied to protect base material during contact with surrounding. One important application in engineering is to protect a boat hull. The coating is applied to boat hull to prevent a decrease of mechanical properties of base materials particularly with corrosive seawater. Composite coating is applied since the composite coating provides better protection compared to paint coating. Additionally, sandblasting prior to composite coating is worked out to improve the mechanical properties of the coating. This work investigated the influence of the projection angle of the sandblasting process on the shear strength of the coated surface. The projection angle of sandblasting was varied from 30 to 90 °. The result shows that a higher projection angle decreases the strain strength of the coating surface. The experiment work showed that the shear strength of 30°, 45 °, 60 °, and 90°projection angle are 1.02, 0.66, 0.38, and 0.24 MPa, respectively.